Assessment of safety compliance towards OSHA 1994 among Malaysian maintenance contractors / Huraizah Arshad and Noraini Johari - Arshad, Huraizah; Johari, Noraini (2012)
Malaysia is a steadily developing country currently striving to become a developed country with a first class infrastructure by 2020. Towards that vision and mission, various developments have been planned notably in the building construction sector to fulfill the needs of society. In the hectic rush of new developments, building maintenance works should not be neglected. .owadays, various issues on occupational safety and health as well as on the quality of building maintenance standard reflecting weaknesses in safety practices such as building impairments, fires, collapse and failures of building structures have been raised and require immediate attention. Maintenance is vital to keep machines and work environments safe and reliable - lack of maintenance or inadequate maintenance can cause serious and fatal accidents or health problems. Maintenance itself is a high-risk activity and should be carried out without producing any risk and hazards to ensure all the occupants of the building are safe, healthy, and comfortable while not being exposed to any risks during occupation of the building. Hence, in order to delve deeper into the issue of safety compliance in performing building maintenance work, a questionnaire survey was distributed among building maintenance contractors in Kuala Lumpur, Selangor and Johor Bahru.